A right to a risk filled life : understanding and analysis of the risk discourse for consumers in mental health : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey University - Phillips, Ross (Massey University, 2008)
This thesis documents the perspective and discourse of risk for eleven people who identify as someone with lived experiences of mental illness and mental health service use. The thesis followed a participatory methodology and involved consumers in both formulating and conducting the research. Following qualitative research methods some key findings included that there was a correlation between increased exposures to risk during increased acute unwellness; increased exposure to risk because of service use; that the people interviewed wished to have some control and self-responsibility in managing risks, that life was full of risk and that this was quite usual; and importantly, that risk was experienced as a stigmatizing phenomena for the participants. The stigma of risk was such that participants had to develop significant coping strategies to manage others perceptions and deal with the experience of having normal behaviours and emotions considered by others as abnormal and risky. The thesis makes recommendations for consumers, services and mental health service staff and for policy makers. Many of the recommendations consider how understandings of risk and approaches to risk management could alter or increase consumer safety and wellbeing. The thesis additionally includes an analysis of the participatory process that was followed with recommendations made encouraging an increased frequency and strengthened quality of consumer participation in research.
Keywords: Mental Health Services; Citizen participation; Risk factors; Mental illness; Social aspects